(untitled) (ETIMA, 2021)
Abstract This paper presents the speed regulation of a 2.2 kW asynchronous squirrel-cage motor, a product of company Rade Koncar, with the aid of a voltage inverter controlled by the pulse-width modulation principle. The simulation circuit is developed in software Powersim. The exact motor data are input in the simulation model and the operation of the motor is simulated for various operating frequencies of the inverter. As an output, the transient characteristics of speed, current, and torque are obtained at various operating speeds i.e. below and above the rated speed of the motor. The effect of the field weakening is observed at higher operating speeds. Obtained results of speed, torque, and currents are compared with the motor data obtained from the analytical model of the motor and data of the manufacturers of variable speed drives, for operating regimes different than the rated. The simulation can serve as an example that proves the theoretical principles of pulse-wide modulation where the desired motor speed is easily obtained with the variation of frequency of modulating signal of the inverter. Keywords Asynchronous squirrel cage motor, PWM inverter, field –weakening, transient characteristics